Tinjauan Yuridis Terhadap Perjanjian Surrogate Mother Yang Tertuang Dalam Akta Notaris Di Indonesia - Kenyatun Kenyatun (Lex Renaissance, 2020)
This study aims to analyze the legal position of surrogate mother agreement according to the Indonesiam Civil Code and Islamic law and the implementation of surrogate mother agreement made in the form of a notary deed in Indonesia. This is a normative legal research that uses a statutory approach. The results of the study conclude that the surrogate mother agreement in the perspective of civil law is considered invalid because it violates the nature of the object of the agreement while the rental of uterus according to Islamic law is unlawful as confirmed in the fatwa and individual opinions based on the Qur'an. In addition, if the surrogate mother agreement is contained in a notary deed, then the deed becomes null and void.